2009
DOI: 10.2174/1874940200902010028
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Inhibition of Myeloperoxidase by Hydrogen Peroxide: Enhancement of Inactivation Rate by Organic Donor Substrates

Abstract: Abstract:The effects of two hydrazine derivatives (isoniazid and hydralazine) on the inactivation of myeloperoxidase by H 2 O 2 were investigated. Incubation of 20 nM myeloperoxidase with 0.25 mM H 2 O 2 alone caused a time-dependent irreversible loss of tetramethylbenzidine oxidation activity with a pseudo-first order inactivation rate constant of 0.057 min -1 . The hydrazine derivatives increased the inactivation rate in a concentration-dependent manner. Inactivation of the enzyme by H 2 O 2 with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…It was found that hydrogen peroxide is capable of SOD inactivation, yet too slow to be the cause of inactivation under physiological conditions (Escobar et al, 1996). However, relatively higher concentrations of hydrogen peroxides (and hydroperoxides) are capable of substrate peroxidase inactivation (Olorunniji et al, 2009), which was not confirmed by the results of our study. Increased activities of GPx, synergistically acting GR together with lowered concentrations of GSH (especially 6 months after starting therapy) only support the response to oxidative stress conditions (Figure 1 and 2).…”
Section: Resultscontrasting
confidence: 87%
“…It was found that hydrogen peroxide is capable of SOD inactivation, yet too slow to be the cause of inactivation under physiological conditions (Escobar et al, 1996). However, relatively higher concentrations of hydrogen peroxides (and hydroperoxides) are capable of substrate peroxidase inactivation (Olorunniji et al, 2009), which was not confirmed by the results of our study. Increased activities of GPx, synergistically acting GR together with lowered concentrations of GSH (especially 6 months after starting therapy) only support the response to oxidative stress conditions (Figure 1 and 2).…”
Section: Resultscontrasting
confidence: 87%
“…Considering the inability of O 2 .– to cross‐membranes and the lowered requirements for its dismutation according to measured SOD activities (Table ), a decrease in GPx activity suggests lower peroxide formation and thus lower need for their elimination. However, at relatively high concentrations of H 2 O 2 and other hydroperoxides, peroxidases undergo substrate inactivation by the modification of the prosthetic haem group (Olorunniji et al., ). It is still necessary to consider, because GPx activity from the same group measured in the plasma and in kidney mitochondria was not affected, although the significant increase in SOD activity suggests that peroxides had been formed.…”
Section: Discussionmentioning
confidence: 99%